Transport signatures of an Andreev molecule in a quantum dot–superconductor–quantum dot setup - Scherübl, Zoltán; Pályi, András; Csonka, Szabolcs (Beilstein Journal of Nanotechnology, 2019)
Hybrid devices combining quantum dots with superconductors are important building blocks of conventional and topological quantum-information experiments. A requirement for the success of such experiments is to understand the various tunneling-induced non-local interaction mechanisms that are present in the devices, namely crossed Andreev reflection, elastic co-tunneling, and direct interdot tunneling. Here, we provide a theoretical study of a simple device that consists of two quantum dots and a superconductor tunnel-coupled to the dots, often called a Cooper-pair splitter. We study the three special cases where one of the three non-local mechanisms dominates, and calculate measurable ground-state properties, as well as the zero-bias and finite-bias differential conductance characterizing electron transport through this device. We describe how each non-local mechanism controls the measurable quantities, and thereby find experimental fingerprints that allow one to identify and quantify the dominant non-local mechanism using experimental data. Finally, we study the triplet blockade effect and the associated negative differential conductance in the Cooper-pair splitter, and show that they can arise regardless of the nature of the dominant non-local coupling mechanism. Our results should facilitate the characterization of hybrid devices, and their optimization for various quantum-information-related experiments and applications.
Keywords: Andreev bound state; crossed Andreev reflection; elastic co-tunneling; quantum dot

(untitled) - Leijnse, M.; Flensberg, K. (Semicond. Sci. Technol., 2012)

(untitled) - Aguado, R. (Riv. Nuovo Cimento Soc. Ital. Fis., 2017)

(untitled) - Janvier, C.; Tosi, L.; Bretheau, L.; Girit, Ç. Ö.; Stern, M.; Bertet, P.; Joyez, P.; Vion, D.; Esteve, D.; Goffman, M. F.; Pothier, H.; Urbina, C. (Science, 2015)

(untitled) - Byers, J. M.; Flatté, M. E. (Phys. Rev. Lett., 1995)

(untitled) - Deutscher, G.; Feinberg, D. (Appl. Phys. Lett., 2000)

(untitled) - Lesovik, G. B.; Martin, T.; Blatter, G. (Eur. Phys. J. B, 2001)

(untitled) - Recher, P.; Sukhorukov, E. V.; Loss, D. (Phys. Rev. B, 2001)

(untitled) - Leijnse, M.; Flensberg, K. (Phys. Rev. B, 2012)

(untitled) - Sau, J. D.; Sarma, S. D. (Nat. Commun., 2012)

(untitled) - Klinovaja, J.; Loss, D. (Phys. Rev. B, 2014)

(untitled) - Haim, A.; Keselman, A.; Berg, E.; Oreg, Y. (Phys. Rev. B, 2014)

(untitled) - Gaidamauskas, E.; Paaske, J.; Flensberg, K. (Phys. Rev. Lett., 2014)

(untitled) - Keselman, A.; Fu, L.; Stern, A.; Berg, E. (Phys. Rev. Lett., 2013)

(untitled) - Liu, X.-J.; Wong, C. L. M.; Law, K. T. (Phys. Rev. X, 2014)

(untitled) - Clarke, D. J.; Alicea, J.; Shtengel, K. (Nat. Phys., 2014)

(untitled) - San-Jose, P.; Lado, J. L.; Aguado, R.; Guinea, F.; Fernández-Rossier, J. (Phys. Rev. X, 2015)

(untitled) - Lee, G.-H.; Huang, K.-F.; Efetov, D. K.; Wei, D. S.; Hart, S.; Taniguchi, T.; Watanabe, K.; Yacoby, A.; Kim, P. (Nat. Phys., 2017)

(untitled) - Clarke, D. J.; Alicea, J.; Shtengel, K. (Nat. Commun., 2013)

(untitled) - Klinovaja, J.; Yacoby, A.; Loss, D. (Phys. Rev. B, 2014)

(untitled) - Alicea, J.; Fendley, P. (Annu. Rev. Condens. Matter Phys., 2016)

(untitled) - Beckmann, D.; Weber, H. B.; v. Löhneysen, H. (Phys. Rev. Lett., 2004)

(untitled) - Russo, S.; Kroug, M.; Klapwijk, T. M.; Morpurgo, A. F. (Phys. Rev. Lett., 2005)

(untitled) - Cadden-Zimansky, P.; Chandrasekhar, V. (Phys. Rev. Lett., 2006)

(untitled) - Beckmann, D.; v. Löhneysen, H. (Appl. Phys. A: Mater. Sci. Process., 2007)

(untitled) - Hofstetter, L.; Csonka, S.; Nygård, J.; Schönenberger, C. (Nature, 2009)

(untitled) - Herrmann, L. G.; Portier, F.; Roche, P.; Yeyati, A. L.; Kontos, T.; Strunk, C. (Phys. Rev. Lett., 2010)

(untitled) - Hofstetter, L.; Csonka, S.; Baumgartner, A.; Fülöp, G.; d’Hollosy, S.; Nygård, J.; Schönenberger, C. (Phys. Rev. Lett., 2011)

(untitled) - Das, A.; Ronen, Y.; Heiblum, M.; Mahalu, D.; Kretinin, A. V.; Shtrikman, H. (Nat. Commun., 2012)

(untitled) - Wei, J.; Chandrasekhar, V. (Nat. Phys., 2010)

(untitled) - Schindele, J.; Baumgartner, A.; Schönenberger, C. (Phys. Rev. Lett., 2012)

(untitled) - Lambert, N. J.; Edwards, M.; Esmail, A. A.; Pollock, F. A.; Barrett, S. D.; Lovett, B. W.; Ferguson, A. J. (Phys. Rev. B, 2014)

(untitled) - Tan, Z. B.; Cox, D.; Nieminen, T.; Lähteenmäki, P.; Golubev, D.; Lesovik, G. B.; Hakonen, P. J. (Phys. Rev. Lett., 2015)

(untitled) - Sand-Jespersen, T.; Paaske, J.; Andersen, B. M.; Grove-Rasmussen, K.; Jørgensen, H. I.; Aagesen, M.; Sørensen, C. B.; Lindelof, P. E.; Flensberg, K.; Nygård, J. (Phys. Rev. Lett., 2007)

(untitled) - Governale, M.; Pala, M. G.; König, J. (Phys. Rev. B, 2008)

(untitled) - Meng, T.; Florens, S.; Simon, P. (Phys. Rev. B, 2009)

(untitled) - Deacon, R. S.; Tanaka, Y.; Oiwa, A.; Sakano, R.; Yoshida, K.; Shibata, K.; Hirakawa, K.; Tarucha, S. (Phys. Rev. Lett., 2010)

(untitled) - Deacon, R. S.; Tanaka, Y.; Oiwa, A.; Sakano, R.; Yoshida, K.; Shibata, K.; Hirakawa, K.; Tarucha, S. (Phys. Rev. B, 2010)

(untitled) - Pillet, J.-D.; Quay, C. H. L.; Morfin, P.; Bena, C.; Yeyati, A. L.; Joyez, P. (Nat. Phys., 2010)

(untitled) - Futterer, D.; Swiebodzinski, J.; Governale, M.; König, J. (Phys. Rev. B, 2013)

(untitled) - Kim, B.-K.; Ahn, Y.-H.; Kim, J.-J.; Choi, M.-S.; Bae, M.-H.; Kang, K.; Lim, J. S.; López, R.; Kim, N. (Phys. Rev. Lett., 2013)

(untitled) - Chang, W.; Manucharyan, V. E.; Jespersen, T. S.; Nygård, J.; Marcus, C. M. (Phys. Rev. Lett., 2013)

(untitled) - Pillet, J.-D.; Joyez, P.; Žitko, R.; Goffman, M. F. (Phys. Rev. B, 2013)

(untitled) - Kumar, A.; Gaim, M.; Steininger, D.; Yeyati, A. L.; Martín-Rodero, A.; Hüttel, A. K.; Strunk, C. (Phys. Rev. B, 2014)

(untitled) - Schindele, J.; Baumgartner, A.; Maurand, R.; Weiss, M.; Schönenberger, C. (Phys. Rev. B, 2014)

(untitled) - Lee, E. J. H.; Jiang, X.; Houzet, M.; Aguado, R.; Lieber, C. M.; De Franceschi, S. (Nat. Nanotechnol., 2014)

(untitled) - Jellinggaard, A.; Grove-Rasmussen, K.; Madsen, M. H.; Nygård, J. (Phys. Rev. B, 2016)

(untitled) - Lee, E. J. H.; Jiang, X.; Žitko, R.; Aguado, R.; Lieber, C. M.; De Franceschi, S. (Phys. Rev. B, 2017)

(untitled) - Gramich, J.; Baumgartner, A.; Schönenberger, C. (Phys. Rev. B, 2017)

(untitled) - Li, S.; Kang, N.; Caroff, P.; Xu, H. Q. (Phys. Rev. B, 2017)

(untitled) - Žitko, R.; Lim, J. S.; López, R.; Aguado, R. (Phys. Rev. B, 2015)

(untitled) - Bretheau, L.; Wang, J. I.-J.; Pisoni, R.; Watanabe, K.; Taniguchi, T.; Jarillo-Herrero, P. (Nat. Phys., 2017)

(untitled) - Eldridge, J.; Pala, M. G.; Governale, M.; König, J. (Phys. Rev. B, 2010)

(untitled) - Trocha, P.; Weymann, I. (Phys. Rev. B, 2015)

(untitled) - Wrześniewski, K.; Trocha, P.; Weymann, I. (J. Phys.: Condens. Matter, 2017)

(untitled) - Su, Z.; Tacla, A. B.; Hocevar, M.; Car, D.; Plissard, S. R.; Bakkers, E. P. A. M.; Daley, A. J.; Pekker, D.; Frolov, S. M. (Nat. Commun., 2017)

(untitled) - Averin, D. V.; Nazarov, Y. V. (Phys. Rev. Lett., 1990)

(untitled) - Falci, G.; Feinberg, D.; Hekking, F. W. J. (Europhys. Lett., 2001)

(untitled) - Feinberg, D. (Eur. Phys. J. B, 2003)

(untitled) - Bignon, G.; Houzet, M.; Pistolesi, F.; Hekking, F. W. J. (Europhys. Lett., 2004)

(untitled) - Mélin, R.; Feinberg, D. (Phys. Rev. B, 2004)

(untitled) - Sauret, O.; Feinberg, D.; Martin, T. (Phys. Rev. B, 2004)

(untitled) - Kleine, A.; Baumgartner, A.; Trbovic, J.; Schönenberger, C. (EPL, 2009)

(untitled) - Kleine, A.; Baumgartner, A.; Trbovic, J.; Golubev, D. S.; Zaikin, A. D.; Schönenberger, C. (Nanotechnology, 2010)

(untitled) - Schroer, A.; Recher, P. (Phys. Rev. B, 2015)

(untitled) - Nigg, S. E.; Tiwari, R. P.; Walter, S.; Schmidt, T. L. (Phys. Rev. B, 2015)

(untitled) - Hassler, F.; Catelani, G.; Bluhm, H. (Phys. Rev. B, 2015)

(untitled) - Amitai, E.; Tiwari, R. P.; Walter, S.; Schmidt, T. L.; Nigg, S. E. (Phys. Rev. B, 2016)

(untitled) - Walldorf, N.; Padurariu, C.; Jauho, A.-P.; Flindt, C. (Phys. Rev. Lett., 2018)

(untitled) - Fülöp, G.; d'Hollosy, S.; Baumgartner, A.; Makk, P.; Guzenko, V. A.; Madsen, M. H.; Nygård, J.; Schönenberger, C.; Csonka, S. (Phys. Rev. B, 2014)

(untitled) - Fülöp, G.; Domínguez, F.; d’Hollosy, S.; Baumgartner, A.; Makk, P.; Madsen, M. H.; Guzenko, V. A.; Nygård, J.; Schönenberger, C.; Levy Yeyati, A.; Csonka, S. (Phys. Rev. Lett., 2015)

(untitled) - Sothmann, B.; Tiwari, R. P. (Phys. Rev. B, 2015)

(untitled) - Hussein, R.; Jaurigue, L.; Governale, M.; Braggio, A. (Phys. Rev. B, 2016)

(untitled) - Probst, B.; Domínguez, F.; Schroer, A.; Yeyati, A. L.; Recher, P. (Phys. Rev. B, 2016)

(untitled) - Leijnse, M.; Flensberg, K. (Phys. Rev. Lett., 2013)

(untitled) - van der Wiel, W. G.; De Franceschi, S.; Elzerman, J. M.; Fujisawa, T.; Tarucha, S.; Kouwenhoven, L. P. (Rev. Mod. Phys., 2002)

(untitled) - Sprinzak, D.; Ji, Y.; Heiblum, M.; Mahalu, D.; Shtrikman, H. (Phys. Rev. Lett., 2002)

(untitled) - Elzerman, J. M.; Hanson, R.; Greidanus, J. S.; Willems van Beveren, L. H.; De Franceschi, S.; Vandersypen, L. M. K.; Tarucha, S.; Kouwenhoven, L. P. (Phys. Rev. B, 2003)

(untitled) - Sillanpää, M. A.; Lehtinen, T.; Paila, A.; Makhlin, Y.; Roschier, L.; Hakonen, P. J. (Phys. Rev. Lett., 2005)

(untitled) - Duty, T.; Johansson, G.; Bladh, K.; Gunnarsson, D.; Wilson, C.; Delsing, P. (Phys. Rev. Lett., 2005)

(untitled) - Frey, T.; Leek, P. J.; Beck, M.; Blais, A.; Ihn, T.; Ensslin, K.; Wallraff, A. (Phys. Rev. Lett., 2012)

(untitled) - Petersson, K. D.; McFaul, L. W.; Schroer, M. D.; Jung, M.; Taylor, J. M.; Houck, A. A.; Petta, J. R. (Nature, 2012)